EPEN-07. OVEREXPRESSION AND MUTATIONS OF CXORF67 IN 'INFANT-TYPE' POSTERIOR FOSSA TYPE-A (PFA) EPENDYMOMAS. Issue 2 (22nd June 2018) - Orisme, Wilda; Wen, Ji; Tang, Bo; Hübner, Jens-Martin; Wu, Gang; Jia, Sujuan; Easton, John; Haupfear, Kelly; Freibaum, Brian D; Kim, Hong Joo; High, Anthony; Vo, BaoHan; et al.
Abstract: Ependymomas are classified into nine molecular groups by DNA methylation profiling. PFA tumors are most prevalent, present mainly in infants and have poor outcomes. Genomic studies have not identified a recurrent driver mutation in PFA ependymomas. However, PFA ependymomas are characterized by lack of H3 K27 trimethylation (H3K27-me3) and overexpression of CXorf67, a novel gene of unknown function. A review of PF ependymoma sequencing data revealed recurrent mutations in CXorf67 . Subsequent analysis of a large series of ependymomas (n=263) showed that CXorf67 mutations occur in PFA ependymomas at a frequency of 9.4%, but not in non-PFA ependymomas. Targeted sequencing also revealed H3 K27M mutations in PFA ependymomas at a frequency of 3.9%. H3 and CXorf67 mutations were mutually exclusive. We used immunoprecipitation (IP) / mass spectrometry (MS) to study proteins bound to CXorf67 in the Daoy cell line, which overexpresses CXorf67 . EZH2, SUZ12, and EED, core components of the PRC2 complex were identified among enriched peptides and validated through complementary SUZ12 IP/MS. We also showed that modulation of CXorf67 influences H3K27-me3 levels downstream of PRC2, suggesting a link between overexpression of CXorf67 and the altered global epigenetic state in PFA ependymomas through its interaction with PRC2. Enforced reduction of CXorf67 in Daoy cells restored H3K27-me3 levels, while enforced expression of CXorf67 in HEK293T and neural stem cells reduced H3K27-me3 levels. Our results suggest that CXorf67 overexpression may have an oncogenic role in PFA ependymomas, but the selective advantage of CXorf67 mutations is yet to be explained.